Faith-Based Entrepreneurship and Social Capital: Insights from Santripreneur in Indonesian Pesantren - Bernando J Sujibto (Lembaga penelitian dan pengabdian kepada masyrakat, 2025)
The importance of Islamic values in entrepreneurship is increasingly debated in Muslim-majority countries. This study examines the experience of Santripreneur Indonesia in applying religious values alongside entrepreneurial practices. A qualitative methodology is used to document the experiences of participants in the field. The study presents several key findings. First, the internalization of Islamic values within the Santripreneur Indonesia movement occurs both culturally through education and through practical application. Second, Santripreneur Indonesia emphasizes independence as a core principle, encouraging santri and their networks to engage in entrepreneurship individually and collectively. Third, the strength of networking, established and maintained by caretakers (pengasuh), is a critical foundation. This network functions as capital to support Santripreneur Indonesia events, which often involve state institutions and related organizations, and as a medium to enhance field performance